Heterogeneity of network and coding states in mouse CA1 place cells - Matteo Guardamagna; Federico Stella; Francesco P. Battaglia (Cell Reports, 2023)
Summary: Theta sequences and phase precession shape hippocampal activity and are considered key underpinnings of memory formation. Theta sequences are sweeps of spikes from multiple cells, tracing trajectories from past to future. Phase precession is the correlation between theta firing phase and animal position. Here, we reconsider these temporal processes in CA1 and the computational principles that they are thought to obey. We find stronger heterogeneity than previously described: we identify cells that do not phase precess but reliably express theta sequences. Other cells phase precess only when medium gamma (linked to entorhinal inputs) is strongest. The same cells express more sequences, but not precession, when slow gamma (linked to CA3 inputs) dominates. Moreover, sequences occur independently in distinct cell groups. Our results challenge the view that phase precession is the mechanism underlying the emergence of theta sequences, suggesting a role for CA1 cells in multiplexing diverse computational processes.